Performance investigation of proposed adaptive heterogeneity in WSN - Aseel Hameed Al-Nakkash, Dr. (International Journal of Engineering and Technology, 2018)
Recently Wireless Sensor Networks (WSNs) have become the optimal solution for handling many tasks. However, there are many tasks due to their critical situations need continues and a comprehensive monitoring of the environment. Accordingly, judicious designs of such networks are necessary. In this work, an adaptive scheme for enhancing the network performance in terms of load balancing during the heterogeneous WSN life time is proposed. The proposed scheme is based on dynamically modifying the probability of Cluster Heads (CHs) election in order to balance the load during the latest rounds when the network began to lose its power and thus weakening its reliability. The network performance is investigated based on the proposed scheme materialized by many scenarios. And it has shown that, adaptively electing CHs related to the network energy will enable the network to recover its reliability and enhancing the performance in terms of throughput and living nodes.
Keywords: Cluster Head; Heterogeneous WSN; Load Balancing; WSN Throughput; WSN Life Time